Empathy as a counter to political violence: towards a caring society - Maslikova, Iryna (Ukrainian Cultural Studies, 2024)
Background. The article outlines the conceptual landscape of altruism research, which allows explaining the differences between biological, behavioral and psychological altruism, identifying its specific features and mapping out the prospects for interdisciplinary research on empathy. The article highlights the history of the concept of "empathy" and clarifies its difference from sympathy and compassion. Methods. The importance of empathy for the substantiation of normative moral judgments and the formation of motivation to alleviate the suffering of others is revealed on the basis of the findings of modern psychology. Emphasis is placed on the cognitive (the ability to understand the feelings of others) and affectional (the ability to experience the feelings of others as one’s own) characteristics of empathy, which are effective motivational factors for individual assistance to others and which serve as a basis for the formation of political and managerial decisions on institutional assistance to vulnerable groups of people. Results. An attention is focused on the importance of empathy for moral consciousness and moral action. The article considers the possibilities of developing empathy through moral education techniques ("inductive discipline", modelling, discuss dilemma situations, improvement of caring skills through cooperation, "confirmation"), which are being developed by moral psychologists and representatives of care ethics as a new interdisciplinary research field on the formation of caring relationships between citizens. The article reveals the prospects of care ethics in solving problems, which are arising in the practices of health care, social assistance, national defence and security, political protests and active participation in civic life. The research potential of care ethics to analyse the experience of various forms of political violence, which were committed during wars, genocide, and terrorism is determined. Taking into account the contexts of specific acts of political violence will allow us to better understand the causes of political violence, develop algorithms for resolving such conflicts and mechanisms for their prevention. Conclusions. An important factor in countering violence is empathy, which is actualised when acts of violence are documenting and through the perception of works of art, reportages, and literary stories that document the experience of suffering. This practice is necessary for those are involved in the rehabilitation of victims of political terror and genocide, those who seek mechanisms for fair punishment of war criminals and compensation for moral damage to victims of violence, those who build conditions for survivors to live together after the war. Development of empathy creates conditions for mutual trust, respect and assistance, which are the foundations of a caring society.